COMPARISON ANTIOXIDAN ACTIVITY OF RED GINGER (Zingiber officinale var. rubrum) ETANOL EXTRACTION BY MASERATION AND DIGESTI MASERATION METHODS - Merry, Jesica (Jurnal Penelitian Farmasi Dan Herbal, 2024)
The red ginger plant (Zingiber officinale variety rubrum) is a common plant in our surroundings that is used to cure a number of degenerative diseases as well as pain management, antipyretic, and anti-inflammatory conditions. Volatile oil, non-volatile oil and starch substances are part of red ginger. The volatile oil or volatile oil gives ginger its characteristic odor, and the non-volatile oil or oleoresin gives it its bitter taste. Oleoresin, which consists of resin, gingerol, and shogaol, It is an antioxidant needed by the body to prevent free radicals from forming and being harmful to the body. The reason for this is to determine the antioxidant content of red ginger. The extraction methods used were maceration with the process of soaking the material using nonpolar solvents without heating and digestion maceration or kinetic maceration (continuous stirring) using weak heating at 40-50°C. Very strong antioxidant activity was obtained where digestion maceration with an IC50 value of 7,30 was stronger than maceration with an IC50 of 11,90 because heating in digestion maceration opens the tissue in red ginger so that active compounds are extracted out.